The Effect of Parental Participation and Learning Intensity on Student Learning Outcomes in Learning Buddhist Religion in Buddhist High School/Vocational School in West Tangerang - Jory Wangulimala; Sutrisno Sutrisno; Alexander Candra (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
This study aims to analyze the influence of parental participation and learning intensity on student learning outcomes in Buddhist studies at Buddhist Senior High Schools/Vocational High Schools throughout West Tangerang. The research method used is quantitative with an associative approach. The population in this study were students at Buddhist Senior High Schools/Vocational High Schools throughout West Tangerang, with a simple random sampling technique resulting in a sample of 125 respondents. The data analysis technique in this study used descriptive statistical analysis and structural equation modeling (SEM). The results of this study indicate that partially parental participation and learning intensity have a positive and significant effect on student learning outcomes in Buddhist studies at Buddhist Senior High Schools/Vocational High Schools throughout West Tangerang. In addition, simultaneously parental participation and learning intensity have a positive and significant effect on student learning outcomes in Buddhist studies at Buddhist Senior High Schools/Vocational High Schools throughout West Tangerang.